Combined angiography and perfusion using radial imaging and arterial spin labeling - Okell, Thomas W. (Magn Reson Med, 2018)
PURPOSE: To demonstrate the feasibility of a novel noninvasive MRI technique for the comprehensive evaluation of blood flow to the brain: combined angiography and perfusion using radial imaging and arterial spin labeling (CAPRIA). METHODS: In the CAPRIA pulse sequence, blood labeled with a pseudocontinuous arterial spin labeling pulse train is continuously imaged as it flows through the arterial tree and into the brain tissue using a golden ratio radial readout. From a single raw data set, this flexible imaging approach allows the reconstruction of both high spatial/temporal resolution angiographic images with a high undersampling factor and low spatial/temporal resolution perfusion images with a low undersampling factor. The sparse and high SNR nature of angiographic images ensures that radial undersampling artifacts are relatively benign, even when using a simple regridding image reconstruction. Pulse sequence parameters were optimized through sampling efficiency calculations and the numerical evaluation of modified pseudocontinuous arterial spin labeling signal models. A comparison was made against conventional pseudocontinuous arterial spin labeling angiographic and perfusion acquisitions. RESULTS: 2D CAPRIA data in healthy volunteers demonstrated the feasibility of this approach, with good vessel visualization in the angiographic images and clear tissue perfusion signal when reconstructed at 108‐ms and 252‐ms temporal resolution, respectively. Images were qualitatively similar to those from conventional acquisitions, but CAPRIA had significantly higher SNR efficiency (48% improvement on average, P = 0.02). CONCLUSION: The CAPRIA technique shows potential for the efficient evaluation of both macrovascular blood flow and tissue perfusion within a single scan, with potential applications in a range of cerebrovascular diseases.